AI-Assisted Learning in Arabic Grammar: Investigating the Use of ChatGPT and Digital Platforms in Arabic Learning - Rani Ismil Hakim; Isra Hayati Darman; Ade Destri Deviana; Lailatul Qomariyah; Usfiyatur Rusuly; Elvina Gusman (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Artificial intelligence (AI) technologies are increasingly being integrated into language learning; however, empirical evidence regarding their use in Arabic grammar and translation (Nahwu wa Tarjamah/I‘rab) learning remains limited, particularly in Islamic higher education contexts. Existing studies have predominantly focused on general language learning applications, leaving insufficient understanding of how AI-supported platforms facilitate the learning of complex grammatical analysis and translation skills. This study aims to identify the AI-based platforms employed in I‘rab learning and examine their impact on students’ learning experiences and outcomes. A quasi-qualitative design was employed involving 30 fifth-semester students enrolled in the Nahwu course at STAIN Mandailing Natal. Data were collected through classroom observations, questionnaires, and in-depth interviews and analyzed using the Miles and Huberman interactive model. The findings reveal that students utilized four categories of AI-supported resources: digital learning repositories, generative AI applications, machine translation tools, and Arabic grammar support websites. The integration of these technologies enhanced students’ awareness of digital learning resources, promoted autonomous learning practices, increased learning motivation, and received positive instructional support from lecturers. Furthermore, students demonstrated strong academic performance, achieving a mean final course score of 88.2 (A). This study contributes to the growing literature on AI-assisted Arabic language learning by providing empirical evidence of AI’s role as a digital scaffolding tool in facilitating the acquisition of advanced Arabic grammatical and translation competencies.